ANALYSIS OF CHANGES IN THE NEEDS OF MOBILE COMMUNICATION CONSUMERS UNDER THE CONDITIONS OF MARITAL STATE - KOVAL, Svitlana; MYROSH, Yuliia; HRYBYK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
During the war in Ukraine, the need for means of communication and communication became unjustified (the ability to communicate with relatives, connect the emergency response service, etc.), therefore, there is a need to remove bottlenecks in the services of mobile operators, which manifested themselves by special characteristics. and equations of these manifestations in order to satisfy the primary needs of the population, actualized in the conditions of war, as much as possible. Today, difficult times have come to Ukraine: the war, and everything that it brings, destroys the life so familiar to many. With the loss of peace, the country’s population is no longer able to fulfill the levels of basic needs that Abraham Maslow wrote about: lack of a sense of security, loss of housing (permanent residence), power outages, and with it mobile communication. The study of the quality of received mobile communication services, changes in the needs of its consumers is important today, because the restructuring of needs requires modifications in the way they are met. Therefore, the main goal of mobile operators is to satisfy the primary needs of mobile users as best as possible, to support the spirit of the people by filling the "gaps" as best as possible. So, by conducting a survey this year and in 2021, we will be able to better understand the needs of mobile users today and try to find ways to meet them.